Race pattern of women`s 100-m hurdles: Time analysis of Olympic hurdle performance - Tsiokanos, A.; Tsaopoulos, D.; Giavroglou, A.; Tsarouchas, E. (International Journal of Kinesiology & Sports Science, 2017)
For control and effective management of training process in women`s 100-m hurdles event, the coaches, in addition to detailed biomechanical parameters, need also overall, more comprehensive technical parameters, called direct performance descriptors which are used for planning the distribution of an athlete`s efforts over the race. Purpose: The aim of this study was the investigation of the race behavior of elite women sprint hurdlers, on the basis of selected time parameters, and the examination of the existence of a common race pattern in high level hurdle performance. Method: The time data of the race performance between two consecutive Olympic Games were compared. The analyzing subjects consisted of all women 100-m hurdle finalists in Athens 2004 (n = 6) and all women 100-m hurdle finalists (n = 8) and semi-finalists (n = 14) in Beijing 2008. Results: No significant differences were revealed between the two competitions concerning to the means of approach run time, run-in time, intermediate touchdown times, interval times for the hurdle units and the corresponding average velocities. Significant relationship exists between the intermediate times and final performance. The time contribution of the first half of the race to the formation of the final performance is approximately equal to the second one and, generally the standardised time parameters show the existence of a common race pattern in high level hurdle performance. Conclusion: The presented biomechanical data provide coaches and athletes with valuable information about hurdle technique for effective interventions in the training process.